2022
DOI: 10.1039/d2dt00758d
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and electrochemical characterization of a Pr4+ imidophosphorane complex and the redox chemistry of Nd3+ and Dy3+ complexes

Abstract: The molecular tetravalent oxidation state for praseodymium is observed in solution via oxidation of the anionic trivalent precursor [K][Pr3+(NP(1,2-bis-tBu-diamidoethane)(NEt2))4] (1-Pr(NP*)) with AgI at -35 C. The Pr4+ complex is characterized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…25,26 Even when measured oxidation potentials for Tb III and Pr III complexes are nominally equivalent (−0.72 V versus Fc/Fc + ), like in La Pierre and co-workers' [Ln III (NP(1,2,-bis-t Bu-diamidoethane)-(NEt 2 )) 4 ] − complexes, the Pr IV complex evades isolation and is unstable at room temperature in contrast to the Tb IV analogue. 27,31 Lucena et al previously reported on reactions of the LnO 2+ complexes studied in the present work, there with H 2 O to yield LnOH 2+ . In that work it was found that TbO 2+ reacted very inefficiently, with PrO 2+ reacting even slower, at a barely detectable rate.…”
Section: ■ Concepts and Methodssupporting
confidence: 52%
See 2 more Smart Citations
“…25,26 Even when measured oxidation potentials for Tb III and Pr III complexes are nominally equivalent (−0.72 V versus Fc/Fc + ), like in La Pierre and co-workers' [Ln III (NP(1,2,-bis-t Bu-diamidoethane)-(NEt 2 )) 4 ] − complexes, the Pr IV complex evades isolation and is unstable at room temperature in contrast to the Tb IV analogue. 27,31 Lucena et al previously reported on reactions of the LnO 2+ complexes studied in the present work, there with H 2 O to yield LnOH 2+ . In that work it was found that TbO 2+ reacted very inefficiently, with PrO 2+ reacting even slower, at a barely detectable rate.…”
Section: ■ Concepts and Methodssupporting
confidence: 52%
“…Standard electrode potentials, properties of solid materials, solution electrochemistry, and isolable molecular complexes all point to a (slightly) greater stability of Tb IV versus Pr IV . ,, , For example, predicted E 0 (IV/III) for Tb are 0.1–0.4 V less positive than for Pr; and under highly alkaline and concentrated solutions of weak-field complexing ligands, Tb 4+ has a reduction potential of +1.3 V compared to +1.4 V for Pr 4+ . ,, Solid PrF 4 decomposes to PrF 3 at 363 K, whereas TbF 4 is stable to at least 623 K. ,, Mazzanti and co-workers recently isolated [Ln IV (OSiPh 3 ) 4 (MeCN) 2 ] for Ln = Pr and Tb, reporting that the Pr IV complex was reduced at a substantially more positive potential (−0.38 V versus Fc/Fc + ) than the Tb IV complex (−0.96 V versus Fc/Fc + ), indicating higher stability of Tb IV versus Pr IV . , Even when measured oxidation potentials for Tb III and Pr III complexes are nominally equivalent (−0.72 V versus Fc/Fc + ), like in La Pierre and co-workers’ [Ln III (NP­(1,2,-bis- t Bu-diamidoethane)­(NEt 2 )) 4 ] − complexes, the Pr IV complex evades isolation and is unstable at room temperature in contrast to the Tb IV analogue. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the modeling of a transition to a LMCT state has remained a significant challenge because it requires an accurate description of both the ground state, which is usually a magnetic level and the LMCT excited state, which involves a change of (oxidation) state for the metal and one or more ligands. For this reason, while several multireference ab initio studies of 4f–4f excitations in lanthanoid complexes , and 4f–5d transitions in doped glasses have been reported, ab initio studies of LMCT remain scarce in the literature due to their complexity. , This work sets a foundational framework based on both theoretical and solid-state experimental approaches to investigate LMCT excited states for lanthanoid complexes.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, while several multireference ab initio studies of 4f−4f excitations in lanthanoid complexes 25,38−45 and 4f−5d transitions in doped glasses 46−48 have been reported, ab initio studies of LMCT remain scarce in the literature due to their complexity. 49,50 This work sets a foundational framework based on both theoretical and solidstate experimental approaches to investigate LMCT excited states for lanthanoid complexes.…”
Section: ■ Introductionmentioning
confidence: 99%